Analisis Faktor-Faktor yang Mempengaruhi Tingkat Kemiskinan di Provinsi Gorontalo Tahun 2016-2020 - Hairus Rahman; Dwi Susilowati; Riski Angga Pramuja (Program Studi Ekonomi Pembangunan Universitas Muhammadiyah Malang, 2022)
The purpose of this study was to analyze the population, education, and economic growth of the poverty level in the district/city of Gorontolo province. This thesis uses quantitative research with panel data types sourced from the Central Statistics Agency of Gorontalo province and the number of samples is 6 districts/cities. The analysis used in this research is panel data regression which is processed through Stata 16 and the selected model is Random Effect. In this study, the results are as follows: 1). The variables of population, education, and economic growth partially have a negative and significant influence on the poverty level in the district/city of Gorontalo province 2). The variables of population, education, and economic growth simultaneously have an influence on the poverty level in the Regency/City of Gorontalo province.